ANALISIS PENGARUH JANGKAUAN WI-FI, DUKUNGAN TEKNIS, SUMBER DATA DAN MOTIVASI SUPERVISOR UNTUK MENGAPLIKASIKAN PROGRAM TERHADAP KETERCAPAIAN TARGET SUPERVISORY BEHAVIOR SEBAGAI INDIKATOR KEBERHASILAN PROGRAM BBM 7UP (BUMA BISA MOBILE – 7 ULTIMATE PROFILES) DI PT BUKIT MAKMUR MANDIRI UTAMA - Subagyo, Andreas Muwardi Septe; Hariadi, Agustinus (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
BUMA applies BBM 7UP Program. The BBM 7UP Program is an advanced process (further development) of the Supervisory Behavior Development Program; which is done by embedding daily behavior from the beginning to the end of the working shift, as well as coaching activities in accordance with the behavior indicators that have been set by each function. In the next process BBM 7UP program is run using tools in the form of a device which installed program BBM 7UP. In its implementation, there was a lack of achievement and a downward trend in the achievement of supervisory behavior on the BBM 7UP program at PT Bukit Makmur Mandiri Utama (BUMA) sites that implemented the program, referring to 2017 data, as well as lack of achievement and decreasing trend in achievement of the supervisor performance operation division BUMA; year to date October 2017. The research methodology used in this study is causal and associative design. Causal design is to find out the variables that are the cause (independent variable) and the variables that become the result (dependent variable) and analyze the influence of variables or how a variable can affect other variables, where the independent variable consists of: wi-fi range, support technical, data sources and supervisor motivation to apply the program are analyzed to the dependent variable, namely achievement of BBM 7UP supervisory behavior targets on BBM 7UP program, using multiple linear regression analysis. From the research that has been done, the findings are obtained: Motivation of supervisors to apply the program has the greatest influence on the achievement of supervisory behavior targets among other research variables.